2008
DOI: 10.1021/ja077286t
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Compound I-like Reactivity of a Bare High-Valent Oxo Iron Porphyrin Complex:  The Oxidation of Tertiary Amines

Abstract: The mechanisms of oxidative N-dealkylation of amines by heme enzymes including peroxidases and cytochromes P450 and by functional models for the active Compound I species have long been studied. A debated issue has concerned in particular the character of the primary step initiating the oxidation sequence, either a hydrogen atom transfer (HAT) or an electron transfer (ET) event, facing problems such as the possible contribution of multiple oxidants and complex environmental effects. In the present study, an ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 114 publications
(81 reference statements)
5
65
0
Order By: Relevance
“…In analogy with previous findings and reasoning about the corresponding iron complex, [12] we ascribe this result to the presence of an isomeric species unfit to release an oxygen atom, most likely a species oxidised on the porphyrin ligand that may be depicted as…”
Section: Dedicated To the Centenary Of The Italian Chemical Societysupporting
confidence: 80%
“…In analogy with previous findings and reasoning about the corresponding iron complex, [12] we ascribe this result to the presence of an isomeric species unfit to release an oxygen atom, most likely a species oxidised on the porphyrin ligand that may be depicted as…”
Section: Dedicated To the Centenary Of The Italian Chemical Societysupporting
confidence: 80%
“…Later, the Yoshizawa group studied the kinetic isotope effect of the C H bond activation of alkane [26,27] and the mechanism of camphor hydroxylation by Cpd I [28]. Since then, P450-catalyzed substrate metabolism has been widely studied using the DFT method, including alkane hydroxylation [28,29], alkene epoxidation [30][31][32][33], aromatic hydroxylation [34][35][36][37][38], S-, N-, O-oxidation and dealkylation [39][40][41][42][43][44], dehalogenation of perhalogenated benzene [45], prostaglandin H 2 isomerization [46], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Settings that are different for tandem MS (MS/MS) include: microscans=3, injection time=50, 500, or 1000 ms. -, corresponding to the homolytic catalytic pathway. To our knowledge, these results represent the first direct observation of the Fe-porphyrin homolytic catalytic pathway by MS (previous FT-ICR ESI-MS studies observed the radical cation iron oxo 1a) [42,43].…”
Section: Mass Spectrometrymentioning
confidence: 51%
“…-DESI-MS, we studied iron (Fe) porphyrin-catalyzed hydroxylations such as Fe tetra(pentafluorophenyl)-porphyrin (Fe-TPFPP, 1) hydroxylation of substrate propranolol 2 (proposed mechanism shown in Scheme 1 [41]), previously analyzed by ESI Fourier transform ion cyclotron resonance MS [42,43]. Experimental results show that TM 2 -DESI provides the ability to spatially separate reagents and to specify their order of introduction into microdroplet reaction vessels, reducing off-path processes such as oxidant-mediated hydroxylation of 2 (Scheme 1).…”
mentioning
confidence: 99%